Presence, power, and promise : the role of the spirit of God in the Old Testament - Firth, David G.; Wegner, Paul D. (Downers Grove, Ill. : IVP Academic, 2011)
From the first verses of Genesis, the Spirit of God makes a dramatic appearance in the Bible. However, despite the importance of the Spirit in the Old Testament, it has been the focus of surprisingly little scholarship. In response, this volume assembles a host of premier Old Testament scholars to address various aspects of the subject. Major thematic essays and studies of relevant biblical texts are arranged in eight main sections: orientation of the Ancient Near Eastern context; the Spirit and its relation to creation, wisdom, creativity, prophecy, leadership and the future, and finally the Spirit at Qumran.
Breath, wind, spirit and the Holy Spirit in the Old Testament / Richard E. Averbeck -- The Ancient Near Eastern background of the Spirit of the Lord in the Old Testament / John H. Walton -- The Spirit and creation / Robert L. Hubbard, Jr. -- Spirit and wisdom / Tremper Longman III -- Job 27:3 : the Spirit of God in my nostrils / Rosalind Clarke -- Spirit and the psalmist in Psalm 51 / Daniel J. Estes -- Spirit and presence in Psalm 139 / Jamie A. Grant -- Spirit of wisdom or Spirit of God in Proverbs 1:23 / Lindsey Wilson -- Bezalel and Oholiab : Spirit and creativity / Richard S. Hess -- The view from the top : the Holy Spirit in the prophets / Daniel I. Block -- Is Balaam's donkey the real prophet (Numbers 24:1-4)? / John N. Oswalt -- The Spirit of Yahweh in Isaiah 11:1-9 / Hilary Marlow -- Isaiah 48:16 : a Trinitarian enigma? / Paul D. Wegner -- Joel's promise of the Spirit / Erika Moore -- The Spirit and leadership : testimony, empowerment and purpose / David G. Firth -- The Samson saga and spiritual leadership / Eugene H. Merrill -- Is Saul also among the prophets? Saul's prophecy in 1 Samuel 19:23 / David G. Firth -- The 'Spirit of the Lord' in 2 Kings 2:16 / Robert B. Chisholm, Jr. -- The Spirit and the future : a canonical approach / Willem VanGemeren and Andrew Abernethy -- The Spirit and the future in the Old Testament : restoration and renewal / Robin Routledge -- The Holy Spirit at Qumran / Geert W. Lorein.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Holy Spirit -- Biblical teaching